Transient Receptor Potential-Vanilloid (TRPV1-TRPV4) Channels in the Atlantic Salmon, Salmo salar. A Focus on the Pineal Gland and Melatonin Production - Nisembaum, Laura Gabriela; Loentgen, Guillaume; L’Honoré, Thibaut; Martin, Patrick; Paulin, Charles-Hubert; Fuentès, Michael; Escoubeyrou, Karine; Delgado, María Jesús; Besseau, Laurence; Falcón, Jack (Frontiers in Physiology, 2022)
Fish are ectotherm, which rely on the external temperature to regulate their internal body temperature, although some may perform partial endothermy. Together with photoperiod, temperature oscillations, contribute to synchronizing the daily and seasonal variations of fish metabolism, physiology and behaviour. Recent studies are shedding light on the mechanisms of temperature sensing and behavioural thermoregulation in fish. In particular, the role of some members of the transient receptor potential channels (TRP) is being gradually unravelled. The present study in the migratory Atlantic salmon, Salmo salar, aims at identifying the tissue distribution and abundance in mRNA corresponding to the TRP of the vanilloid subfamilies, TRPV1 and TRPV4, and at characterizing their putative role in the control of the temperature-dependent modulation of melatonin production - the time-keeping hormone - by the pineal gland. In Salmo salar, TRPV1 and TRPV4 mRNA tissue distribution appeared ubiquitous; mRNA abundance varied as a function of the month investigated. In situ hybridization and immunohistochemistry indicated specific labelling located in the photoreceptor cells of the pineal gland and the retina. Additionally, TRPV analogues modulated the production of melatonin by isolated pineal glands in culture. The TRPV1 agonist induced an inhibitory response at high concentrations, while evoking a bell-shaped response (stimulatory at low, and inhibitory at high, concentrations) when added with an antagonist. The TRPV4 agonist was stimulatory at the highest concentration used. Altogether, the present results agree with the known widespread distribution and role of TRPV1 and TRPV4 channels, and with published data on trout (Oncorhynchus mykiss), leading to suggest these channels mediate the effects of temperature on S. salar pineal melatonin production. We discuss their involvement in controlling the timing of daily and seasonal events in this migratory species, in the context of an increasing warming of water temperatures.